Comparing different sperm separation techniques for ART, through quantitative evaluation of p53 protein - Salvatore Raimondo; Tommaso Gentile; Mariacira Gentile; Francesca Donnarumma; Giusy Esposito; Alessia Morelli; Stefania De Filippo; Felice Cuomo (Wolters Kluwer Medknow Publications, 2020)
Context: In the last 10 years, assisted reproductive technologies (ARTs) have offered infertile couples an opportunity to complete their reproductive project. However, the high failure rate could be explained with the complex human reproduction system. In ART, the decrease of the success is due to the conditions far from the natural ones. Aims: The aim of this study is to evaluate deoxyribonucleic acid (DNA) damage of spermatozoa before and after selection procedures, using a new technique able to quantize sperm DNA damage. Settings and Design: They were involved 43 males domiciled permanently in two areas with different Environmental Impact, HEI (high environmental impact) and LEI (Low environmental impact), they are aged between 24 and 31 years with various degrees of dyspermia. Subjects and Methods: The 43 males were divided into two groups: 21 in Group A (EIL) and 22 in Group B (EIH). The samples must be aliquoted into parts of 0.5 mL: Group (a) Control, no processing; Group (b) Swim-up (SUP) from semen; Group (c) classic SUP; Group (d) density gradient centrifugation (DGC). All samples were subjected to a quantitative dosage of p53 protein, before and after processing. Statistical Analysis Used: For the development of the probability and significance of the data, the Student's t-test was used. Results: From our data, it emerges that Groups D and B provide a superior quality about motility, vitality, and apoptosis indexes compared to other conventional techniques. In Group B, apoptosis is comparable to Group D, but they have slightly lower about motility and vitality. Group C is the one that has lower parameters than the other techniques. Regarding the evaluation of p53 protein, the results are conflicting with the evaluation of apoptosis; in fact, in Group D, the values are significantly higher than the other techniques. Conclusions: Sperm separation is an important moment in ART techniques. From our data, it emerges a greater fragility of DNA in the male spermatozoa who reside permanently in areas with high environmental impact.